2014
DOI: 10.1016/s1995-7645(14)60019-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance pattern of Mycobacterium tuberculosis isolates from patients of five provinces of Iran

Abstract: The prevalence of drug resistance in this study area underscoring the need for further enforcement of TB control strategies in the Iran. Drug susceptibility testing for all TB cases to provide optimal treatment, establishing advanced diagnostic facilities for rapid detection of MDR-TB and continuous monitoring of drug resistance are recommended for prevention and control of drug-resistant TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 12 publications
4
47
0
Order By: Relevance
“…The incidence of tuberculosis from 2004 to 2012 is shown in Figure 1. In 2014, a research by Nasiri et al, involving five different provinces of Iran, revealed that of 252 TB cases, 41 (16.3%) were resistant to at least one drug and 16 (6.3%) were MDR, underscoring the need for further enforcement of TB control strategies including BCG vaccination in the country (36). Genetic variety of BCG vaccine strains may change the resulting immunological response to it.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of tuberculosis from 2004 to 2012 is shown in Figure 1. In 2014, a research by Nasiri et al, involving five different provinces of Iran, revealed that of 252 TB cases, 41 (16.3%) were resistant to at least one drug and 16 (6.3%) were MDR, underscoring the need for further enforcement of TB control strategies including BCG vaccination in the country (36). Genetic variety of BCG vaccine strains may change the resulting immunological response to it.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in a recent survey, 41 (16.3%) of 252 M. tuberculosis isolates collected from the patients of different parts of Iran, including five provinces, were resistant to at least one anti-tuberculosis drugs (40). This study indicated lower drug resistance rates in Iran than the studies conducted in Turkey, Iraq, and Pakistan with the drug resistance rates of 21.1%, 29.7%, and 64% respectively (15,60).…”
Section: Multidrug-resistant Tuberculosis In Iranmentioning
confidence: 51%
“…In the studies conducted in Iranian settings, drug resistance to streptomycin has been found to have the highest proportion among anti-tuberculosis drugs, followed by isoniazid with 23% resistance in new cases of tuberculosis (23,40,41). The high prevalence of streptomycin resistance isolates may be due to the previous usage of other aminoglycosidal drugs for the treatment of different infectious diseases, like brucellosis, which can result in crossresistance (23).…”
Section: Treatment Policy and Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the patients with AFB-positive after 2 months was 44.8 years, while the mean age of the patients with AFB-negative after 2 months was 40.8 years, and 45.3% of the subjects were above 46 years; no statistically significant difference was observed (P value = 0.123).In the study by Nassiri on 6426 patients in Iran, the mean age of the patients was 45 years (18). In the study by Soudbakhsh in Emam Khomeini hospital of Tehran, definitive relationship between the change sputum smear and age was not reached (19).…”
Section: Discussionmentioning
confidence: 91%